Endovascular Versus External Targeted Temperature Management for Patients With Out-of-Hospital Cardiac Arrest. Issue 3 (21st July 2015) - Deye, Nicolas; Cariou, Alain; Girardie, Patrick; Pichon, Nicolas; Megarbane, Bruno; Midez, Philippe; Tonnelier, Jean-Marie; Boulain, Thierry; Outin, Hervé; Delahaye, Arnaud; Cravoisy, Aurélie; Mercat, Alain; et al.
<x xml:space="preserve">Abstract</x> Background— Targeted temperature management is recommended after out-of-hospital cardiac arrest. Whether advanced internal cooling is superior to basic external cooling remains unknown. The aim of this multicenter, controlled trial was to evaluate the benefit of endovascular versus basic surface cooling. Methods and Results— Inclusion criteria were the following: age of 18 to 79 years, out-of-hospital cardiac arrest related to a presumed cardiac cause, time to return of spontaneous circulation <60 minutes, delay between return of spontaneous circulation and inclusion <240 minutes, and unconscious patient after return of spontaneous circulation and before the start of cooling. Exclusion criteria were terminal disease, pregnancy, known coagulopathy, uncontrolled bleeding, temperature on admission <30°C, in-hospital cardiac arrest, immediate need for extracorporeal life support or hemodialysis. Patients were randomized between 2 cooling strategies: endovascular femoral devices (Icy catheter, Coolgard, Zoll, formerly Alsius; n=203) or basic external cooling using fans, a homemade tent, and ice packs (n=197). The primary end point, that is, favorable outcome evaluated by survival without major neurological damage (Cerebral Performance Categories 1–2) at day 28, was not significantly different between groups (odds ratio, 1.41; 95% confidence interval, 0.93–2.16; P=0.107). Improvement in favorable outcome at day 90 in favor of the endovascular group did not reach significance (odds ratio, 1.51; 95% confidence interval, 0.96–2.35; P=0.07). Time to target temperature (33°C) was significantly shorter and target hypothermia was more strictly maintained in the endovascular than in the surface group (P<0.001). Minor side effects directly related to the cooling method were observed more frequently in the endovascular group (P=0.009). Conclusion— Despite better hypothermia induction and maintenance, endovascular cooling was not significantly superior to basic external cooling in terms of favorable outcome. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00392639.